The Rhetoric of Black Mayors : In Their Own Words. - Atwater, Deborah F., 1949- (Rowman & Littlefield Pub. Group, 2010)
The Rhetoric of Black Mayors explores the rhetorical and practical efforts of Black mayors in building coalitions to win elections and govern cities. Atwater discusses and analyzes the process of creating coalitions by each mayor by dealing with thenews coverage of the mayors by both the black and mainstream press. As a unique feature, the text includes interviews with most of the mayors included in The Rhetoric of Black Mayors. These mayors are from cities on the east coast, ranging from thelarge city of Philadelphia to the small city of Glenarden, Maryland. This text covers successful admini.